THE IMPLEMENTATION OF CIPP EVALUATION MODEL ON A MEMORY-ENHANCED ENGLISH LEARNING PROGRAM - Senia Almayah,Yayan Sudrajat, Yovan Pino Putra,Basuki Wibawa,Rusmono, Natalie Marie Dancey,Claudia Brookes (International Journal of Advanced Science and Technology, 2020)
This preliminary qualitative research aims to evaluate the necessity for an English Community-Learning Program (PPKBI / Program Pembelajaran Komunitas Bahasa Inggris) in Sukawangi Village, West Java. This free-of-charge learning program is unique because not only it applies an eclectic memory techniques in order to make learning to be meaningful and memory enhancing but also the combination of in-door and out-door learning settings. Subjects were students of grade VII, VIII and IX of SMP N 3 Sukawangi. Data of the program were obtained through recorded interviews to all stakeholders of the program, including students, school English teacher, principal and parents and a field observation of English lessons in the school. Data validation was conducted by triangulation method. The CIPP model evaluation instrument revealed the similarities of the result obtained from different sources, so that it can be concluded that such English program is needed and the CIPP model evaluation instrument is suitable for doing evaluation on the program.